2019
DOI: 10.1371/journal.pone.0222354
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cells ameliorate complement induced inflammatory cascade and improve renal functions in a rat model of ischemia-reperfusion induced acute kidney injury

Abstract: IntroductionThe primary rational for using mesenchymal stromal cells (MSCs) to rejuvenate damaged tissue is mostly based on their capacity to trans-differentiate and repair injured organs. However, previous studies have demonstrated that MSCs are beneficial even at very early stages, before differentiation and proliferation can be expected. The aim of the current study was to investigate the multifaceted immunological effects of systemically administrating MSCs in the setting of acute kidney injury (AKI) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…An increase in the M2 macrophage CD68/CD163 population. As discussed, these M2 macrophages have anti-inflammatory and proregenerative properties ( 28 , 32 ).…”
Section: Treatment With Mesenchymal Stromal Cells In Acute Kidney Injmentioning
confidence: 99%
See 3 more Smart Citations
“…An increase in the M2 macrophage CD68/CD163 population. As discussed, these M2 macrophages have anti-inflammatory and proregenerative properties ( 28 , 32 ).…”
Section: Treatment With Mesenchymal Stromal Cells In Acute Kidney Injmentioning
confidence: 99%
“…Following IRI, MSCs migrate to the injured site and alleviate the damage ( 21 ). Studies have demonstrated that MSCs have beneficial effects even at very early stages after their migration, before any differentiation and proliferation can be expected ( 28 ). This observation has led to the understanding that the MSC's early beneficial effects are related to their paracrine activity in the surrounding tissue ( 29 , 30 ).…”
Section: The Biology Of Mesenchymal Stromal Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excluding hydronephrotic animals would be very important if the unilateral renal I-R model with the removal of contralateral kidney is exploited. Researchers have performed the above-mentioned experimental model by removing the right (Zilberman-Itskovich et al, 2019) or left (Ar'Rajab et al, 1994) kidney. As the right-sided F I G U R E 5 Effects of unilateral hydronephrosis on the L-carnitine (a) and furosemide (b) concentrations in the plasma after a single subcutaneous administration.…”
Section: T a B L E 2 Kidney Functional Parameters During The 8-week Omentioning
confidence: 99%